The impact of aerobic and isometric exercise on different measures of dysfunctional high-density lipoprotein in patients with hypertension. (29th August 2020) - Pagonas, Nikolaos; Vlatsas, Stergios; Bauer, Frederic; Seibert, Felix S; Sasko, B; Buschmann, I; Ritter, O; Kelesidis, Theodoros; Westhoff, Timm H
Abstract: Background: Exercise training increases high-density lipoprotein (HDL) cholesterol, but its effect on HDL function is unclear. In hypertensives, exercise improves endothelial dysfunction, which is related to HDL function. In the present study, we assess for the first time the effects of different exercise modalities on two cell-free assays of HDL function. Design: The study was conducted as a prospective randomized controlled trial in 75 hypertensive patients. Methods: Patients were randomized in three groups: (a) handgrip isometric training five times weekly; (b) placebo-handgrip; and (c) aerobic exercise training at least three times per week. HDL function was assessed in serum samples at baseline and after 12 weeks of training by two independent assays that determine the proinflammatory phenotype (haptoglobin content) of a specific amount of HDL (Haptoglobin-HDL [HPHDL]) and oxidized HDL (HDLox) as a measure of reduced antioxidant function of HDL. HDL function measures were normalized by the measures of a pooled control of sera from healthy participants and by HDL-C levels (normalized ratio, no units). Results: Aerobic exercise led to significant reduction of the HDLox from 0.99 ± 0.27 to 0.90 ± 0.29 (no units, p = 0.03). The HPHDL did not change in any training group. Changes of HDLox correlated with reduction of the systolic blood pressure only after aerobic exercise ( R = 0.64, p = 0.03). Conclusions: Aerobic but not isometric exercise improves the antioxidant function of HDL in patients with hypertension. This improvement correlates positively with reductions of blood pressure.